Where there was no COVID-19: strengthening health systems response to disease threats in Tabora, Tanzania - Shegufta S Sikder; Amani Idfonce (Inishmore Laser Scientific Publishing Ltd, 2022)
# Background In May 2020, the international non-governmental organization Cooperative for Assistance and Relief Everywhere (CARE) sought to enable health systems in Tanzania to address COVID-19 health response. CARE leveraged existing partnerships with the Ministry of Health, Community Development, Gender, Elderly and Children and the President's Office of Regional Administration and Local Government in the largest geographic region of Tanzania, Tabora Region. At the time, the government declared Tanzania to be free from COVID-19 and did not permit partners to implement COVID-19 programming. In this context, CARE implemented integrated health systems strengthening support for government response to not only COVID-19 but also other infectious diseases. # Methods We describe program implementation using monitoring reports generated by CARE colleagues to inform planning of integrated health programs that are gender-responsive. The initiative supported regional and local capacity building on infection prevention and control, household hygiene, infectious disease surveillance, and response to gender-based violence according to Tanzania's national guidelines. These efforts utilized existing platforms and workers, including health care workers, community health workers, community groups, and government health management teams at the regional and district levels. # Results CARE supported Tabora Region to develop 20 regional trainers who provide on-site mentorship and supportive supervision on infection prevention and control to health care workers. Nearly all (93%) trained community members on Violence Against Women and Children (VAWC) Committees expressed confidence in response to Gender-Based Violence in accordance with Tanzania's National VAWC Action Plan. Trained Community Health Workers continue to link communities to health information and services. # Conclusions Implementation of a holistic health system strengthening approach with a gender lens positioned Tabora Region for response to infectious disease threats including COVID-19. Program managers seeking to address COVID-19 in their contexts should strengthen health systems at regional and district levels as well as community structures to enable resilient response to disease threats including but not limited to COVID-19.